2019
DOI: 10.1038/s41467-019-09495-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlled repeatable scrambling and induced-sorting of building blocks between cubic assemblies

Abstract: Separation of a homogeneous mixture of different components to reach an ordered out-of-equilibrium state in solution has attracted continuous attention. While this can be achieved using external chemical fuels or photo energy, an alternative energy source is heat. Here we realize a temperature-controlled cycle of transitions between ordered and disordered states based on a mixture of two kinds of building blocks that self-assemble into cubic structures (nanocubes). An almost statistical mixture of nanocubes (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…[7] Stepwise syntheses exploiting orthogonal reactivities can afford lowsymmetry organic cages, [6,36,37] but this limits the scalability of the resulting materials.Alternatively,low-symmetry architectures may be obtained by purification of complex mixtures, but this is al aborious process and may be unachievable on ap reparative scale due to reconfiguration of the desired products. [38][39][40][41] Ar ecent study showed that low-symmetry cages can be formed using al ower-symmetry aldehyde precursor,b ut the presence of multiple structural isomers precluded the unambiguous characterisation of the cage products. [42] We sought to avoid these problems by designing an alternative single-step route to low-symmetry imine-based cages.W eused mixtures of multiple aldehyde precursors with different geometries to investigate their self-sorting behaviour,s creening for combinations that led to the selective formation of low-symmetry cages.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Stepwise syntheses exploiting orthogonal reactivities can afford lowsymmetry organic cages, [6,36,37] but this limits the scalability of the resulting materials.Alternatively,low-symmetry architectures may be obtained by purification of complex mixtures, but this is al aborious process and may be unachievable on ap reparative scale due to reconfiguration of the desired products. [38][39][40][41] Ar ecent study showed that low-symmetry cages can be formed using al ower-symmetry aldehyde precursor,b ut the presence of multiple structural isomers precluded the unambiguous characterisation of the cage products. [42] We sought to avoid these problems by designing an alternative single-step route to low-symmetry imine-based cages.W eused mixtures of multiple aldehyde precursors with different geometries to investigate their self-sorting behaviour,s creening for combinations that led to the selective formation of low-symmetry cages.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of multiple weak interactions give rise to great thermal stability of the nanocubes, which do not disassemble into the monomers at all at even higher temperature than the boiling point of water 17 . These stable nanocubes are attractive for their use towards molecular functions 20,21,22 , but their extremely high stability prevents us from determining the thermodynamic parameters for the self-assembly of the nanocubes to precisely discuss the effect of the weak intermolecular interactions. To slightly decrease the stability of the nanocube, we designed GSAs where a methoxy group is introduced on the periphery of the hexaphenylbenzene (HPB) core ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If polymers switch association partners in response to external stimuli and environments, reversible control of the narcissistic self-sorting and co-self-assembly is achieved using identical binary polymer blends. 24 From such a motivation, we examine the selfassembly of the binary blends of amphiphilic random copolymers carrying different hydrophilic groups in water. Because the size and structures of ionic polymer self-assemblies are often affected by salts and pH in aqueous media, we focus on the combination of ionic copolymers and neutral PEG copolymers and eventually discover unprecedented reversible co-self-assembly/self-sorting systems of simple binary polymer micelles in water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In living organisms, nano- and micro-structured self-assemblies with different structures and functions are simultaneously formed via the precise and dynamic association of amphiphilic biomolecules in complex media. , Those natural self-assemblies are often responsive to environments and external stimuli such as pH and ionic strength to perform functions via the dynamic or reversible transformation of their association structures and partners: gene expression from DNA, transportation of phospholipids between organelles, polymerization of tubulin into microtuble and depolymerization, among many others. Such a selective multicomponent self-assembly is called “self-sorting”, high-fidelity recognition of self from nonself. Inspired by nature, chemists have developed artificial self-sorting systems with synthetic molecules such as well-defined supramolecular compounds, in which those molecules are precisely designed to afford specific intra- or intermolecular interactions (e.g., hydrophobic, hydrogen bonding, Π–Π stacking) and recognition by molecular size and shape, steric effects, and chirality. …”
Section: Introductionmentioning
confidence: 99%